COMPREHENSIVE MIXED-METHODS STUDY: KNOWLEDGE, ATTITUDES, AND PRACTICES OF STREET GIRL ADOLESCENTS TOWARD HIV AND AIDS PREVENTION - Mulyana, Desi Nurlaela; Mukaromah, Nahdiyatul; Wulandari, Lukmi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
HIV and AIDS continue to represent substantial public health challenges among marginalized populations, particularly among street-connected adolescent girls who experience limited access to comprehensive reproductive health education and are exposed to adverse socio-economic conditions. This study sought to evaluate the knowledge, attitudes, and preventive actions of HIV/AIDS among female teenagers residing in the streets of Bekasi Regency. A sequential explanatory design with a mixed-methods approach was implemented. During the quantitative phase, 30 people were recruited using purposive and snowball sampling approaches. The qualitative phase comprised in-depth interviews with ten important informants to help contextualize the quantitative findings. The majority of respondents were in late adolescence (over 15 years old) (60%), had completed junior secondary education (50%), and worked in informal street jobs, mostly as street performers (57%). A mere 17% of interviewees stated that they had previously received HIV/AIDS counseling. Approximately 47% of respondents had a moderate grasp of HIV/AIDS, but more than 52.5% had negative views. Furthermore, the majority (55%) reported participating in preventative measures to a considerable extent. Qualitative findings revealed persistent misconceptions about HIV transmission channels, stigmatizing views toward HIV patients, and widespread feelings of fear and humiliation about HIV testing and participation in educational activities. In Bekasi Regency, street-involved adolescent females shown a sufficient level of awareness and participated in certain preventive actions; yet, unfavorable attitudes concerning HIV/AIDS persisted. These findings underscore the urgent need for integrated, community-based, and youth-centered HIV prevention interventions that explicitly address stigma reduction and promote the adoption of protective behaviors.